Exploring the molecular mechanisms of Drosophila dTRIM32 implicated in pathogenesis of Limb-Girdle Muscular Dystrophy 2H - Bawa, Simranjot (Kansas State University, 2017)
The E3 ubiquitin ligase TRIM32 is a member of tripartite motif (TRIM) family of proteins involved in various processes including differentiation, cell growth, muscle regeneration and cancer. TRIM32 is conserved between vertebrates (humans, mouse) and invertebrates (Drosophila). The N-terminus of this protein is characterized by a RING domain, B-box domain, and Coiled-Coil region, while the C-terminus contains six NHL repeats. In humans, mutations that cluster in the NHL domains of TRIM32 result in the muscle disorders Limb-Girdle Muscular Dystrophy type 2H (LGMD2H) and Sarcotubular Myopathy (STM). Mutations in the B-box region cause Bardet-Biedl Syndrome (BBS), a clinically separate disorder that affects multiple parts of the body. A comprehensive genetic analysis in vertebrate models is complicated by the ubiquitous expression of TRIM32 and neurogenic defects in TRIM32-/- mutant mice that are independent of the muscle pathology associated with LGMD2H. The model organism Drosophila melanogaster possesses a TRIM32 [dTRIM32/Thin (Tn)/Abba] homolog highly expressed in muscle tissue. We previously showed that dTRIM32 is localized to Z-disk of the sarcomere and is required for myofibril stability. Muscles form correctly in Drosophila tn mutants, but exhibit a degenerative muscle phenotype once contraction ensues. Mutant or RNAi knockdown larvae are also defective in locomotion, which mimics clinical features associated with loss of TRIM32 in LGMD2H patients. It is predicted that mutations in the NHL domain either affect protein structure or are involved in protein-protein interactions. However, the molecular mechanism by which these mutations affect the interaction properties of dTRIM32 is not understood. Biochemical pulldown assays using the bait fusion protein GST-dTRIM32-NHL identified numerous dTRIM32 binding proteins in larval muscle tissue. Many key glycolytic enzymes were present in the dTRIM32 pulldowns and not in control experiments. Glycolytic genes are expressed in the developing Drosophila musculature and are required for myoblast fusion. Strikingly, many glycolytic proteins are also found at the Z-disk, consistent with dTRIM32 localization. Our biochemical and genetic studies provide evidence that there is direct interaction between dTRIM32 and glycolytic proteins (Aldolase and PGLYM). dTRIM32 also regulates glycolytic enzyme levels and protein localization at their sites of action. These data together suggest a role for dTRIM32 in coordinating glycolytic enzyme function, possibly for localized ATP production or to maintain muscle mass via glycolytic intermediates.
Keywords: LGMD2H; Thin; Glycolytic enzymes